The myth of Chap Goh Meh and the lanterns in 3D animation - Chai, Teck Hua, (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Due to the rapid growth in our country, young generations nowadays spent most of their daily lives to earn for a living. Even during leisure time they spent the day sitting in front of the computer. Thus, they do not have any time left to listen to their old folks’ storytelling about the past or about the myth and legend of their culture. As a result, the myth behind Chinese culture is slowly forgotten. Therefore, the purpose of this research is to study the myth, culture, and tradition that related to Chap Goh Meh. Based on the research a 3D animation will be created to tell the origin of Chap Goh Meh and its relation to the lanterns.